Polysaccharides in copra meal: extraction conditions, optimisation and characterisation - Sritrakul, N.; Keawsompong, S. (International Journal of Agricultural Technology, 2021)
Extraction conditions of polysaccharides from copra meal were optimised using an orthogonal experimental design. The characterisation of copra meal polysaccharides (CMP) was explored. Optimal extraction conditions were NaOH concentration 16% (w/v), solid-liquid ratio 1:40 (w/v), extraction temperature 70 oC and extraction time 10 h. Under these conditions, extraction yield of polysaccharides was 50.7% (w/w), closed to the predicted value of 50.3%. HPLC analysis revealed mannose as the main sugar, accounting for 99% of total sugar in CMP. FT-IR analysis demonstrated that CMP was mainly composed of polysaccharides. Results suggested alkaline extraction as an efficient method for extraction of polysaccharides from CM and CMP as raw material in the pharmaceutical, biomedical, feed and food industries